Al-â€˜UyÅ«b al-á¸¤arakiyyah wa al-â€˜UyÅ«b al-BayÄniyyah â€˜inda al-JÄá¸¥iáº“ - Muflihah, Muflihah (IAIN Salatiga, 2021)
Al-Jahiz is an Arabic linguist discussing ancient and modern linguistic theories, but most of the current generation ((Arabic linguists) do not know much about him. This study aimed to examine the concept of Al-Jahiáº“ on disabilities of kinetics (Al-harakiyah) and disclosure (Al-Bayaniyah) in using language. The method used was descriptive qualitative which would describe and analyze in depth the concept of Al-Jahiáº“ in terms of kinetics and disclosure disabilities. The primary data sources were collected through documentation of Al-Jahiz books and others that discussed his findings. Based on the results, it was concluded that: According to Al-Jahiáº“, disabilities of kinetics (Al-harakiyah) include the presence of several movements made by the speaker during speaking or speech indicating turbulence, instability and composure, such as clearing throat or coughing. While the disabilities of disclosure (Al-Bayaniyah) include Al- â€˜Ayyu Al-á¸¥aá¹£ru, Al-Bikâ€™u, Al-Faá¸¥mu, As-SalÄá¹otu, Al-HaÅ¼ru.